2021
DOI: 10.4102/rw.v12i1.298
|View full text |Cite
|
Sign up to set email alerts
|

Using flashcards for English second language creative writing in Grade 1

Abstract: Background: English Second Language (ESL) learners have difficulty constructing sentences due to internalising information in their home language and thereafter translating it into English. Learners who have difficulty speaking English generally encounter problems writing it, which hampers their creative writing ability.Objectives: The purpose of the research was to identify a teaching strategy to facilitate ESL learners with creative writing. This study explored the influence of flashcards on the creative wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 20 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Twenty-two studies on the traditional methods of using non-textual elements were identified. Most of these articles used pictures, visual materials, infographics, posters, photographs, and graphics from language teachers and instructors, and their findings highly emphasized the important role of non-textual elements in supporting ESL and EFL learners in language classrooms, as suggested in many previous studies [7][8][9]15]. These articles described the treatment of non-textual elements in engaging learners in language learning through different types of media with illustrations.…”
Section: E-postersmentioning
confidence: 91%
See 1 more Smart Citation
“…Twenty-two studies on the traditional methods of using non-textual elements were identified. Most of these articles used pictures, visual materials, infographics, posters, photographs, and graphics from language teachers and instructors, and their findings highly emphasized the important role of non-textual elements in supporting ESL and EFL learners in language classrooms, as suggested in many previous studies [7][8][9]15]. These articles described the treatment of non-textual elements in engaging learners in language learning through different types of media with illustrations.…”
Section: E-postersmentioning
confidence: 91%
“…In education studies, non-textual elements, such as pictures, photos, flashcards, videos, and infographics, have a vital function in supporting learning among English as a second language (ESL) and English as a foreign language (EFL) learners. Several studies conducted in education from primary to tertiary levels [6][7][8][9][10] have defined visuals as anything one person observes within a given frame. Our world is visually oriented, and most responses are stimulated non-verbally, with verbal information better processed through visual cues.…”
Section: Introductionmentioning
confidence: 99%
“…Baki, 2020;Bataineh & Alqatnani, 2019;Priyatni, 2020) and creative writing skills (i.e. Cetin & Cetin, 2021;Ghoneim & Elghotmy, 2019;Mathura & Zulu, 2021;Paragas & Francisco, 2020). Other studies attempted to examine the relationship between creative thinking skills and reading as well as listening comprehension skills as the study of Piri (2019) and SUR (2021).…”
Section: Efl Creative Speakingmentioning
confidence: 99%
“…Flashcards have also emerged as valuable tools for improving word context understanding and writing skills (Sartika, 2020;Skarr et al, 2012). By combining images and words, flashcards foster spelling and writing proficiency (Adas & Bakir, 2013;Mathura & B. Zulu, 2021). Repeated exposure to flashcards enhances memory retention, benefiting ESL learners (Miles & Ehri, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Repeated exposure to flashcards enhances memory retention, benefiting ESL learners (Miles & Ehri, 2017). The use of flashcards in English learning, particularly, has proven beneficial and engaging in classroom settings, especially among students new to studying English as a second language (Mathura & Zulu, 2021). Another effective method involves group collaboration, particularly advantageous for non-native English speakers seeking enhanced learning outcomes (Altherr, 2022).…”
Section: Introductionmentioning
confidence: 99%